Clinical Efficacy and Safety of Cox-Maze IV Procedure for Atrial Fibrillation in Patients With Hypertrophic Obstructive Cardiomyopathy - Meng, Yanhai; Zhang, Yanbo; Liu, Ping; Zhu, Changsheng; Lu, Tao; Hu, Enci; Yang, Qiulan; Nie, Changrong; Wang, Shuiyun (Frontiers in Cardiovascular Medicine, 2021)
Objective: Atrial fibrillation is the most prevalent persistent arrhythmia in patients with hypertrophic obstructive cardiomyopathy. Comparative analyses of the safety and effectiveness of septal myectomy with and without surgical ablation are limited. This study aimed to compare the outcomes of septal myectomy with and without the Cox-maze IV procedure in patients with hypertrophic obstructive cardiomyopathy and atrial fibrillation. Methods: Ninety-four patients with hypertrophic obstructive cardiomyopathy and atrial fibrillation who underwent septal myectomy were analysed, we divided it into concomitant Cox maze surgery (Cox-maze group) and no concomitant Cox maze operation (no Cox-maze group). Freedom from atrial fibrillation recurrence and all-cause mortality after surgery were assessed. Results: Freedom from all-cause mortality after septal myectomy at 1, 3, and 5 years was 98.5±1.5% each in the Cox-maze group and 90.8±6.3%, 85.1±8.1%, and 85.1±8.1%, respectively, in the no Cox-maze group. Patients in the no Cox-maze group had lower survival, freedom from atrial fibrillation recurrence off antiarrhythmic drugs, and arrhythmia control rate (including patients with successful antiarrhythmic drug conversion) than those in the Cox-maze group (P=0.046, P=0.040, and P=0.012, respectively). Patients who underwent the Cox-maze IV procedure had lower atrial fibrillation recurrence rate than those who did not (hazard ratio, 0.141; 95% confidence interval, 0.042–0.479; P=0.002).Postoperative increases in left atrial diameters (hazard ratio, 1.099; 95% confidence interval, 1.024–1.179; P=0.009) were associated with atrial fibrillation recurrence. Conclusions: The Cox-maze IV procedure combined with septal myectomy improved mid-term survival and reduced mid-term atrial fibrillation recurrence in patients with hypertrophic obstructive cardiomyopathy and atrial fibrillation. The concomitant Cox-maze IV procedure was associated with a lower atrial fibrillation recurrence in patients with surgical hypertrophic obstructive cardiomyopathy and atrial fibrillation.